Euler-Bernoulli Bending Theory (Pure Bending Moment

)
A

ψ

z M x

M

D dw C dx B

neutral axis

uz = w(x) = vertical deflection of the neutral axis

ux

z
u x = − zψ ( x )
dx

dw

ψ

If the plane AB remains perpendicular to CD

ψ=

dw dx

ux = − z

dw dx

ux = − z dw dx ∂u x d 2w = −z 2 ε xx = ∂x dx If we assume σ yy = σ zz = σ xy = σ yz = 0 1 ⎡σ xx −ν (σ yy + σ zz ) ⎤ ⎦ E⎣ The stress-strain relations give ε xx = d 2w σ xx = − E z 2 dx σ xz = G ⎜ ⎛ ∂u x ∂u z + ∂x ⎝ ∂z ⎞ ⎛ dw dw ⎞ = G⎜ − ⎟=0 ⎟ ⎝ dx dx ⎠ ⎠ .

z d 2w σ xx = − E z 2 dx y z σ xx M y M = − ∫ σ xx z dA A =E d w 2 z dA dx 2 ∫ A 2 A x d 2w = EI 2 dx σ xx = − Mz I neutral axis is at centroid cross-section must be symmetric ∫σ A A xx dA = 0 ∫ zdA = 0 A ∫ σ xx y dA = 0 ∫ y z dA = 0 A .

z Engineering Beam Theory x qz M ( x) z σ xx = − Let I V ( x)Q ( z ) σ xz = − I t ( z) [ Note: we still have u x = − z dw ⎛ dw ⎞ ψ= ⎜ ⎟ dx ⎠ dx ⎝ so that σ xz = 0 (inconsistent) ] M V dM = V ( x) d 2w dx M = EI 2 dx dV = qz ( x ) dx d 4w EI 4 = qz ( x ) dx qz … applied force/unit length on beam in zdirection .

dM = V ( x) dx dV = qz ( x ) dx How are these internal force and bending moment equilibrium relations related to our local equilibrium equations? ∂σ xx ∂σ xy ∂σ xz + + =0 ∂x ∂y ∂z ∂σ xy ∂x + ∂σ yy ∂y + ∂σ yz ∂z =0 ∂σ xz ∂σ yz ∂σ zz + + =0 ∂x ∂y ∂z .

∂σ xx ∂σ xy ∂σ xz + + =0 ∂x ∂y ∂z multiply by z and integrate over the cross-section.M(x) z n nz ny . A ∫z A ⎛ ∂σ ∂σ xx ∂σ dA + ∫ z ⎜ xy + xz ∂x ∂y ∂z A ⎝ ⎞ ⎟ dA = 0 ⎠ or.V(x) ∂f ∫ ∂y dA = A C ∫ ∫ f n y ds A C y ∂f ∫ ∂z dA = A Gauss’ theorem (2-D) f nz ds C . equivalently ⎡∂ ⎤ d ∂ zσ xx dA + ∫ ⎢ ( zσ xy ) + ( zσ xz ) ⎥ dA − ∫ σ xz dA = 0 dx ∫ ∂y ∂z ⎦ A A⎣ A .

consider ∂σ xz ∂σ yz ∂σ zz + + =0 ∂x ∂y ∂z integrating over A ⎛ ∂σ yz ∂σ zz d ∫ σ xz dA + ∫ ⎜ ∂y + ∂z dx A A⎝ -V(x) ⎞ ⎟ dA = 0 ⎠ .− dM + ∫ z ( n yσ xy + nzσ xz ) ds + V ( x ) = 0 dx C z n y Tx( n) Tx( ) = 0 n dM = V ( x) dx Now.

− dV + ∫ (σ yz n y + σ zz nz ) ds = 0 dx C Tz( n ) n Tz( n ) z y C Tz( ) ds = qz ( x ) ∫ n applied force/unit length in zdirection dV = qz ( x ) dx Last remaining equilibrium equation is: ∂σ xy ∂x + ∂σ yy ∂y + ∂σ yz ∂z =0 Integrating over A gives .

∂σ ⎛ ∂σ d σ xy dA + ∫ ⎜ yy + yz dx ∫ ∂y ∂z A A⎝ Vy ⎞ ⎟ dA = 0 ⎠ dVy dx + C ∫ (σ yy n y + σ yz nz ) ds = 0 Ty( n ) Ty ( n) n C Ty( ) ds = q y ( x ) ∫ n applied force/unit length in ydirection z y dVy dx = −q y ( x ) Vy which is identically satisfied if Vy = 0. Ty( ) = 0 n .

Timoshenko Beam Theory A ψ z M x M D dw C dx B neutral axis ψ u x = − zψ ( x ) σ xx = − E z dψ dx ⎛ ∂u ∂u σ xz = G ⎜ x + z ∂x ⎝ ∂z ψ ( x) ≠ dw dx dw dx dw ⎞ ⎞ ⎛ = G ⎜ −ψ ( x ) + ⎟ ⎟ dx ⎠ ⎝ ⎠ better than Euler/Bernoulli but still a constant across the cross-section so introduce a form factor κ 2 .

σ xx = − E z dψ dx σ xz = κ 2G ⎜ −ψ ( x ) + σ yy dw ⎞ ⎛ ⎟ dx ⎠ ⎝ = σ zz = σ xy = σ yz = 0 For bending moment and shear force M = − ∫ zσ xx dA = E A dψ dx z 2 dA = EI ∫ A dψ dx dw ⎞ ⎛ V = − ∫ σ xz dA = −κ 2G ⎜ −ψ + ⎟ ∫ dA dx ⎠ A ⎝ A dw ⎞ ⎛ = −κ 2G ⎜ −ψ + ⎟ A = −σ xz A dx ⎠ ⎝ .

Timoshenko Beam theory Euler-Bernoulli Theory dψ M = EI dx V ( x) dw −ψ ( x ) = − 2 dx κ GA d 2w M = EI 2 dx dw ψ= dx P Example: P x M = .Px L x V=-P dψ = − Px dx Px 2 + C1 EIψ = − 2 EI ψ ( L) = 0 ⇒ ψ = This gives P ⎡ L2 − x 2 ⎤ ⎣ ⎦ 2 EI rotation of the beam cross-section σ xx = Pxz I (same as ordinary beam theory) .

dw V =− 2 +ψ slope of neutral axis κ GA dx P ( L2 − x 2 ) P = 2 + κ GA 2 EI Integrating P ( L2 x − x3 / 3) Px + + C2 w= 2 κ GA 2 EI PL PL3 + + C2 = 0 w( L) = 0 ⇒ 2 κ GA 3EI which gives PL3 PL C2 = w(0) = − − 2 3EI κ GA bending shear deflection due to: − PL3 w ( 0) = 3EI 3E I ⎤ ⎡ 1+ 2 ⎢ κ G AL2 ⎥ ⎣ ⎦ I 1 ⎛h⎞ = ⎜ ⎟ AL2 12 ⎝ L ⎠ 2 For a rectangular section of base b and height h .

Sign up to vote on this title
UsefulNot useful